Evaluating the Effect of Examination Malpractice on Academic Performance among Some Selected Secondary School Students in Zaria LGA, Kaduna State, Nigeria - Yusuf, Ishaq Ashapha; Dauda, Bilkisu Musa; Abamu, Musa; Adah , Esther Hauwa (Kashere Journal of Politics and International Relations, 2025)
The study evaluate the effect of examination malpractice on academic performance among Secondary School Students in some selected schools in Zaria LGA, Kaduna State, Nigeria. The study adopted cross–sectional descriptive design to carry out the research work and a simple random sample was used as a subset of statistical population in which each member of the subset has an equal probability of being chosen. The data collected was subjected to the Cronbach’s Alpha which yielded a correlation coefficient of 0.75. Data was analyzed using descriptive statistics using frequency tables and mean calculations. Findings indicate that examination malpractice has effect on academic performance among secondary school student (with aggregate mean of 3.08 and 3.00 in both Al-Hudahuda and GGSS Pada respectively. Lack of effective supervision during examination, lack of preparation for the examination and poor attendance of classes by students were identified as the major causes while various devices such as bringing prepared answers were also identified. Some suggestions were made for preventing examination malpractice. Based on the findings made, it is therefore concluded that examination malpractice is a problem affecting student academic performance among secondary school students, which encourages laziness in students where students no longer depend on themselves but on machineries and external materials. The recommendations such as ensuring that only formally registered candidates sit for the examination, making frequent unannounced visits by officials of examination centers.